Implementasi Metode Topsis dalam Pemilihan Lokasi Batching Plant Proyek Jalan Tol Trans Sumatera Ruas Indrapura-Kisaran - Triana Nasution; Ahmad Perwira Mulia; Gina Cynthia R Hasibuan (Syntax Corporation Indonesia, 2023)
Rigid pavement is one of the main works in the construction of toll road projects, which has a large volume and a certain work time. This requires high productivity in ready-mix concrete to support the work. PT. PP Presisi (Tbk), as one of the subcontractors for the Indrapura-Kisaran Trans Sumatra Toll Road Project, uses a Batching Plant (BP) to produce ready-mix concrete. It is hoped that establishing a Batching Plant (BP) will not only be able to supply concrete but also reduce the planned project budget. One of the factors that supports achieving this is selecting the right location. This study uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to determine the most appropriate location by determining five criteria, 14 sub-criteria, and three alternative locations. This method uses a decision matrix where the best alternative result is the one with the closest distance to the positive ideal solution and the farthest distance to the negative ideal solution. Based on the calculation results, the weight of each alternative is obtained, namely location 1 (0,810), location 2 (0,900), and location 3 (0,159), so that the best alternative location is location 2.